2018
DOI: 10.18178/ijfe.4.1.1-7
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Native Inulin and Oligofructosis Addition to Flour and Its Effects on the Rheological Characteristics of the Dough

Abstract: The aim of this paper was to study the effect of native inulin (IN) addition and oligofructosis (FOS) addition in wheat flour of 1250 type on gluten quality, dough rheological properties and amylase activity. The wheat flour has been enriched with IN and FOS in a proportion of 0-10%. The gluten quality were analyzed by it extensibility and elasticity. The dough rheological properties were analyzed with a Farinograph device the fallowing characteristic being determinate: water absorption, time of development, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In the study of Kaya (2018), the stretching and relaxation values of refined durum wheat were 82.50 s and 534 BU, respectively. Gluten extensibility was higher in wheat samples with native inulin in percentages of 2.5-7.7 % (571-535 s) than in the control dough (499 s) (Codina et al, 2018).…”
Section: Glutograph-e Valuesmentioning
confidence: 82%
“…In the study of Kaya (2018), the stretching and relaxation values of refined durum wheat were 82.50 s and 534 BU, respectively. Gluten extensibility was higher in wheat samples with native inulin in percentages of 2.5-7.7 % (571-535 s) than in the control dough (499 s) (Codina et al, 2018).…”
Section: Glutograph-e Valuesmentioning
confidence: 82%
“…The results of the effect of inulin and bran addition on Farinograph parameters for the mixture of flour (Table 2) shows that increasing inulin addition caused a significant decrease in water absorption due to the dilution effect of inulin on gluten. Substitution of flour by inulin may cause weakening of dough since it does not cooperate in gluten formation, therefore it must decrease the added water to keep on the dough consistency (Codina et al, 2018). The results also showed that increasing inulin increases development time which may attribute to the competition on the water between inulin and gluten causes slowing the formation of the dough gluten network.…”
Section: Rheological Test Farinographmentioning
confidence: 90%